KEKERASAN TERHADAP PEREMPUAN DALAM KUMPULAN CERPEN KITAB KAWIN KARYA LAKSMI PAMUNTJAK: KRITIK SASTRA FEMINIS IDEOLOGIS: Array - Cahyani, Risna Windika; Mulasih, Mulasihmu (DIALEKTIKA JURNAL PENDIDIKAN BAHASA INDONESIA, 2022)
This type of research is a qualitative research with descriptive method. The subject of this research is a collection of short stories Kitab Kawin by Laksmi Pamuntjak. Data collection techniques using reading techniques and note-taking techniques. Data collection instrument using data cards. Data analysis techniques include data collection, raw data description, data reduction, data categorization, and relationships between categories.The result show that the forms of violence agaist women found in the collection of short stories Kitab Kawin by Laksmi Pamuntjak consist of domestic violence namely: physical violence, emotional violence, and economic violence consisting of: sexual and non-sexual violence.